The Façade of Voice Opportunity and Intragroup Conflict - Shah, Syed Imad; Shahjehan, Asad; Afsar, Bilal (UI Scholars Hub, 2016)
The positive consequences of offering employees opportunities to express their opinions about the matters, concerns, and decisions related to their roles have been largely recognized (Bellavance, Landry, & Schiehll, 2013). These include a sense of ownership, inclusion, fairness of decisions, respect, and increased decisions acceptance by employees. However, rarely do any write about the potential negative outcomes of such organizational policies, specifically if they are deceitfully implemented. This research argues that under conditions where managers disregard the appropriate benefits of such policies, but implement them anyway for an apparent semblance of employee-consideration or due to organizational policy directives, this may lead their employees to be distrustful of such actions and consequently of the managers who implement them. This perceived deception of managers will lead to negative effects of these opportunities where employees are given a chance to voice their opinions, rather than foster positive benefits they have been designed for. In this research we studied the negative effects of such dubious implementation of this useful managerial strategy among the employees and managers of selected industries. We developed a survey to gather data from 317 respondents. Our findings suggest that the perceived negative effects of such mock opportunities results in employees’ increasingly lowered participative behaviour in such opportunities and increasingly higher conflict within organization.